2017
DOI: 10.1016/j.gheart.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Community Health Workers for CVD Prevention in LMIC

Abstract: Community health workers (CHW) may be effective in tackling the burden of cardiovascular diseases in low- and middle-income countries (LMIC). This review examines whether CHWs can improve the identification and control of cardiovascular risk factors in LMIC. We searched for studies that used CHW as a basis for cardiovascular risk factor management. Our search yielded 11 articles that targeted cardiovascular risk factor assessment, hypertension, diabetes, smoking, diet and physical activity. There were 4 random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 27 publications
(18 reference statements)
4
68
0
1
Order By: Relevance
“…Because the majority of those persons received a linkage appointment, SEARCH correctly referred a total of 7,978 people across the three sites: 82.7% of the proportion with confirmed HTN (Table 2). To our knowledge, although small studies have demonstrated the feasibility of using non-physician workers for HTN control in low-and middle-income countries [14,14,16,17], no population-wide HTN screening initiative on SEARCH's scale has previously been evaluated for care fidelity or outcomes, although these initiatives have become more common in recent years [14,15,16,17,46,47,48]. Moreover, in Eastern and Western Uganda, SEARCH demonstrates that supervised nonphysician providers can provide consistent clinical care for HTN according to established algorithms, and retain patients over time, achieving treatment rates comparable to high-income countries [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the majority of those persons received a linkage appointment, SEARCH correctly referred a total of 7,978 people across the three sites: 82.7% of the proportion with confirmed HTN (Table 2). To our knowledge, although small studies have demonstrated the feasibility of using non-physician workers for HTN control in low-and middle-income countries [14,14,16,17], no population-wide HTN screening initiative on SEARCH's scale has previously been evaluated for care fidelity or outcomes, although these initiatives have become more common in recent years [14,15,16,17,46,47,48]. Moreover, in Eastern and Western Uganda, SEARCH demonstrates that supervised nonphysician providers can provide consistent clinical care for HTN according to established algorithms, and retain patients over time, achieving treatment rates comparable to high-income countries [49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrates community-level programs to screen and treat CVD risk factors in sub-Saharan Africa are efficacious and cost-effective. Most successful models have leveraged nurses, community health workers, and other non-physicians [14,15,16,17]. Recent studies demonstrate that programs for control of HIV can be leveraged for the control of chronic diseases such as HTN [18,19], though quantitative data on care linkage, blood pressure control, and other operational outcomes are scarce [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are usually of a similar socioeconomic background as their patients, which may allow more effective attenuation of the asymmetry of information between patients and the world of healthcare 20. A few studies that have targeted individual cardiovascular risk factors using CHWs have shown promising results 21. However, given the multiplicity of risk factors with high prevalence, progress will likely hinge on the ability of CHWs to successfully mitigate multiple cardiovascular risk factors, thus ensuring a cost-effective holistic approach to community cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Even within cardiovascular disease, as of 2017, a systematic review of CHWs-driven interventions found "no studies . that looked at combined cardiovascular risk management" as opposed to management of isolated risk factors [12]. And yet, in the case of RHD, natural complementarities with broader cardiovascular disease management abound, such as the use of echocardiography to diagnose and characterize other forms of heart failure, fluid and volume management, and anticoagulation for nonvalvular atrial fibrillation.…”
Section: Principle 1: Rheumatic Heart Disease Care Should Be Integratmentioning
confidence: 99%